Impact of Topical Nepafenac on Macular Thickness after Phacoemulsification with Intraocular Lens Implantation in Patients without Diabetic Retinopathy - Arooj Amjad, Muhammad Shaheer, Hassan Tariq, Ammarah Rasheed , Arooj Amjad, Muhammad Shaheer, Hassan Tariq, Ammarah Rasheed (Journal of Rawalpindi Medical College, 2023)
Objective: To study the effect of post-operative Non-Steroidal Anti-inflammatory (NSAID) eye drops on macular thickness in patients without diabetic retinopathy measured by Optical Coherence Tomography (OCT) after cataract surgery. Study Design: Quasi-experimental study. Place & Duration of Study: Ophthalmology Department/Lahore General Hospital, Lahore from 15-01-2019 to 31-12-2021. Materials & Methods: Diabetic patients without retinopathy who required cataract surgery for visual rehabilitation were included in the study. They were then divided into two groups. Group A included patients who received routine steroid+antibiotic post-operative drops while Group B comprised patients who received nepafenac (0.1%) eye drops eight hourly in addition to routine post-operative eye drops. All patients underwent standard phacoemulsification and intraocular lens implantation followed by the use of NSAID eye drops for a month. OCT measurements were done pre-operatively, 7 and 28 days post-operatively. Results: Comparison of central macular thickness between groups was significant at (Pre & 7-day post-op) and insignificant at (7th day & 28th day post-op) and (Pre & 28th day post op) i.e. 0.043, 0.834, and 0.084 respectively. However, a difference in mean central macular thickness was significant in all follow-up periods i.e. 0.003, 0.006, and 0.000 Conclusion: Post-operative NSAID in diabetic patients without retinopathy leads to a significant decrease in macular thickness as compared to those who do not receive post-operative NSAID after cataract surgery. Keywords: Phacoemulsification, Optical Coherence Tomography, Non-steroidal Anti-Inflammatory Agents.